Awareness of science and technology roles towards socioeconomic development - Cuong, Nguyen Tien; Long, Hoang Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Intuitive awareness of science and technology (S&T) roles towards production appeared early. Tough binding of S&T and production was emphasized in many economic doctrines. Up to now, the practical awareness of this issue, however, remains limited in many aspects. There exist many reasons to explain the fact why the awareness of S&T roles towards socio-economic development is a long and complicated process. Namely, S&T makes impacts not only directly to actual production processes but also indirectly to global aspects of production activities; there are so many components of production activities falling under impacts from S&T such as labors, production means and materials. Impacts from S&T may be strong but unequally dispatched and it is also difficult to evaluate impacts/contributions of S&T to economic activities. There exists certain gaps between S&T research and application activities and between the rightness and usefulness in scientific research. There are also difficulties in S&T development management. International experience shows that there are concrete solutions to settle difficulties and pro-actively to promote the awareness of S&T roles towards socio-economic development. Code: 14120201